Development and Evaluation of an Isolated Resonant Converter for Auxiliary Power Supply in DC Traction - Bhajana, V. V. S. K.; Drabek, P. (Engineering, Technology & Applied Science Research, 2019)
This paper presents the implementation and evaluation of an isolated resonant converter and also compares the efficiencies of hard and soft switching isolated converter topologies using high-frequency transformer for auxiliary power supplies in DC traction. The half-bridge DC-DC converter with resonant network has been tested under zero voltage switching (ZVS), zero current switching (ZCS) operations, and also dead time variation of the power switches improving the overall system efficiency. This paper provides guidelines for a cost effective DC-DC converter design based on discrete 1200V/40A IGBTs driven with high switching frequency. That would allow optimization of passive elements by reducing their mass making the converter suitable for traction application. Simulations and test results of an experimental setup with output power up to 3kW are presented. The overall system efficiency of the ZVS and ZCS operations of half-bridge LLC DC-DC converter were compared with a classic hard switching topology.